Phase-field model of deformation twin-grain boundary interactions in hexagonal systems. (November 2020) - Hu, Xin; Ji, Yanzhou; Heo, Tae Wook; Chen, Long-Qing; Cui, Xiangyang
Abstract: A phase-field model for describing dynamic interactions between deformation twins and grain boundaries in a hexagonal close packed (HCP) metal is established. It is applied to simulating the coupled evolution mechanisms of grains and twins in magnesium (Mg) by probing the transmission of { 10 1 ¯ 2 } deformation twins across grain boundaries. We analyze the effect of the strain relaxation near a grain boundary, which is related to the geometric compatibility arising from the misorientation angle between adjoining grains. Phase-field simulations demonstrate that twin transmission across a grain boundary into a neighboring grain leads to grain boundary migration towards the neighboring grain with a reduced grain boundary width. The preferred nucleation site of new twin variant in the neighboring grain is related to the elastic interaction energy distribution. These predicted transmission behaviors agree well with existing experimental observations and molecular dynamics simulations. By analyzing set of systematic phase-field simulation results, we establish a rotation-angle-related twin variant selection rule for analyzing the transmission of { 10 1 ¯ 2 } deformation twins across grain boundaries in Mg and its alloys. Graphical abstract: Image, graphical abstract